Silver nanoparticles induce SH-SY5Y cell apoptosis via endoplasmic reticulum- and mitochondrial pathways that lengthen endoplasmic reticulum-mitochondria contact sites and alter inositol-3-phosphate receptor function. (15th March 2018) - Li, Lin; Cui, Jiahui; Liu, Zi; Zhou, Xuejiao; Li, Zengqiang; Yu, Yang; Jia, Yuanyuan; Zuo, Daiying; Wu, Yingliang
Graphical abstract: Highlights: AgNPs induce SH-SY5Y cell apoptosis by activating ER stress. AgNPs increase the length of ER-mitochondria contact sites. AgNPs alter inositol-3-phosphate receptor function. ER-mitochondria interactions are involved in apoptosis induced by AgNPs. Abstract: Silver nanoparticles (AgNPs) have many medical and commercial applications, but their effects on human health are poorly understood. The aim of this study was to assess the effect of AgNPs on the human neuroblastoma cell line SH-SY5Y and to explore their potential mechanisms of action. We found that AgNPs decreased SH-SY5Y cell viability in a dose- and time-dependent manner. Exposure to AgNPs activated endoplasmic reticulum (ER) stress, as reflected by upregulated expression of glucose-regulated protein 78 (GRP78), phosphorylated PKR-like endoplasmic reticulum kinase (p-PERK), phosphorylated eukaryotic translation initiation factor 2α (p-eIF2α), C/EBP homology protein (CHOP), spliced X-box binding protein-1 (XBP1), and phosphorylated inositol-requiring enzyme (p-IRE), all of which are involved in the cellular unfolded protein response. Prolonged exposure of cells to AgNPs damaged calcium (Ca 2+ ) homeostasis, increased the length of contact sites between the ER and mitochondria, altered IP3 R function by the increased levels of phosphatase and tensin homolog deleted on chromosome ten (PTEN) in the ER and enhanced mitochondrial Ca 2+ uptake. Finally, Ca 2+ overload and disrupted homeostasis in the mitochondria triggered apoptotic cell death. Our results suggest that caution should be exercised in the use of AgNPs in humans.